改进的造血干细胞和祖细胞疗法 (2016)
本发明提供了改进的用于细胞治疗的方法。特别地，本发明提供具有改进的植入和归巢性质的经改变的造血干细胞和/或祖细胞的治疗组合物，以及制备所述治疗组合物的方法。本发明进步提供了改善造血干细胞和祖细胞移植的功效的方法，包括向需要造血系统重建的个体中植入所述治疗组合物。 The invention provides improved methods for cell therapy. In particular, the invention provides therapeutic compositions of modified hematopoietic stem and/or progenitor cells having improved engraftment and homing properties, and methods of making the therapeutic composition. The invention further provides methods of improving the efficacy of hematopoietic stem and progenitor cell transplantation including transplanting the therapeutic composition to subjects in need of hematopoietic system reconstitution.